The blissful taste of Andaki - Villarino, Ma Eliza J (2024)
The blog highlights the impact of Andaki chocolate, produced sustainably by cocoa farmers in Caquetá, Colombia, in collaboration with CGIAR’s Low-Emission Food Systems and AgriLAC Resiliente initiatives. Sourced from deforestation-free cocoa, Andaki embodies the flavors and quality of Colombian cocoa, reflecting the environmental focus of Colombia's cocoa value chain. Research efforts aim to improve farmers' access to green financing, such as Colombia’s "obras por impuestos," enabling investment in post-harvest facilities and other sustainable practices. The Andaki bar symbolizes progress toward zero-deforestation cocoa that meets international standards and enhances market access.